Responses of Koliella antarctica to light changes - La Rocca N; Morosinotto T; Moro I; Sciuto K; Andreoli C; Rascio N (Società Italiana di Biologia Vegetale (SIBV), 2010)
Preliminary data on the acclimation of Koliella antarctica to different light intensities are shown.